The Effect Of Vocabulary Cards Strategy On The Achievement Of Fifth-Grade Primary School Students In Arabic Grammar (Journal of the College of Basic Education, 2025)
This research aims to identify (the impact of the vocabulary cards strategy on the achievement of fifth grade students in the subject of Arabic grammar), and to verify the goal of the research, the researcher developed the following null hypothesis:) There is no statistically significant difference at the level of -between the average achievement scores of students of the ( experimental group studying Arabic grammar with a strategy (vocabulary cards) and the average achievement scores of students of the control group studying Arabic grammar in the traditional way The researcher randomly selected her research sample consisting of (60) primary/secondary schoolgirls belonging to the General Directorate of Karkh II education in Baghdad governorate with (30) female students in the experimental grloup and (30) femlale studenlts in the controli group and rewarded the researcher between the two research groups in the following variables:: (Chronological age calculated in months, academic achievement of parents, final Arabic language grades of the previous academic year and IQ test scores) then the researcher tried to adjust a number of extraneous variables that the previous literature indicated that they may affect this type of experimental designs. The researcher herself studied the students of the two experimental groups according to the strategy (vocabulary cards), and the control in the traditional way during the duration of the experiment, which lasted a semester, which is the first semester of the academic year (2024-2025), the researcher prepared a final ) a paragraph of the Test as a tool for her research, consisting of ( type of multiple test, applied it to the two research groups At the end. of the experiment, the researcheir useid the following statistical methods the Samir Nof test, the Levin test and the T-test for twoi independent samples, the coefficient of difficulty of paragraphs, the coefficient of discrimination, the effectiveness of erroneous alternatives, the alpha-cronbach equation, and the effect sizeEquatkion. After analyzing the data, the research resulted in the following result:The presence of a statistically significant difference at the level between the average achievement scores of (050,) of significance schoolgirls of the experimental group and the control group and in favor of the experimental group